2022
DOI: 10.1038/s41598-022-17923-4
|View full text |Cite
|
Sign up to set email alerts
|

CX-5461 causes nucleolar compaction, alteration of peri- and intranucleolar chromatin arrangement, an increase in both heterochromatin and DNA damage response

Abstract: In this study, we characterize the changes in nucleolar morphology and its dynamics induced by the recently introduced compound CX-5461, an inhibitor of ribosome synthesis. Time-lapse imaging, immunofluorescence and ultrastructural analysis revealed that exposure of cells to CX-5461 has a profound impact on their nucleolar morphology and function: nucleoli acquired a compact, spherical shape and display enlarged, ring-like masses of perinucleolar condensed chromatin. Tunnels consisting of chromatin developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Our results showed that CX-5461 exhibits the strongest inhibitory effects on c- MYC transcription, which can be attributed to its multifaceted mechanisms of action, including strong c-MYC promoter G4s unfolding inhibition, the ability to intercalate into dsDNA, RNA polymerase I inhibition, chromatin remodeling . Notably, our recent findings indicate that CX-5461 also exhibits a strong affinity for double-stranded DNA ( K d = 0.5 μM) .…”
Section: Discussionmentioning
confidence: 66%
“…Our results showed that CX-5461 exhibits the strongest inhibitory effects on c- MYC transcription, which can be attributed to its multifaceted mechanisms of action, including strong c-MYC promoter G4s unfolding inhibition, the ability to intercalate into dsDNA, RNA polymerase I inhibition, chromatin remodeling . Notably, our recent findings indicate that CX-5461 also exhibits a strong affinity for double-stranded DNA ( K d = 0.5 μM) .…”
Section: Discussionmentioning
confidence: 66%
“…For example, CX-5461 is also known as an RNA polymerase inhibitor and induces alternation of heterochromatin arrangement and DNA damage. 66 Further characterization of the G4s' selective stabilization properties is important to the rational design of G4 selective ligands. Notably, PDS and 360A, the two most widely used G4 ligands, showed moderate dsDNA binding (K d = 22.5 and 48.7 μM) and <0.01 ligands/bp intercalation in the presence of 1 μM ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Even if these ligands have higher affinity to G4s ( K d = 10 –8 –10 –6 M) than dsDNA (Table ), the nonselective binding of G4-targeting ligands to genome dsDNA at micromolar concentrations can be >0.1 ligands/bp and thus may also contribute to cytotoxicity and affect biological processes such as replication and transcription. For example, CX-5461 is also known as an RNA polymerase inhibitor and induces alternation of heterochromatin arrangement and DNA damage . Further characterization of the G4s’ selective stabilization properties is important to the rational design of G4 selective ligands.…”
Section: Discussionmentioning
confidence: 99%
“…1D). In addition to inhibiting Pol I transcription initiation, CX-5461 can also induce alterations in rRNA gene chromatin structure and provoke replication stress that activates ATM/ATR signaling within the nucleoli (18,37,38). Increased phosphorylation of checkpoint kinase 1 (CHK1) at S345 was observed in p53 WT AMO-1 cells while activation of checkpoint kinase 2 (pCHK2 at T68) was absent due to the lack of CHK2 (Fig.…”
Section: Cx-5461 Impairs Ribosome Biogenesis and Activates Ddr Signal...mentioning
confidence: 99%